Gender inclusivity of engineering students' experiences of workplace learning : final report. - Male, Sally (Office for Learning and Teaching, 2015)
To the detriment of Australian society and people, women in Australia remain under-represented among engineering students and even more among engineers. Engineering workplaces have features that are gender non-inclusive. Therefore efforts to improve engineering education by increasing industry engagement might further discourage female engineering students. This is the final report from a project that contributed towards ensuring that industry engagement is gender inclusive. Focusing on personal interactions, the project investigated the workplace experiences of male and female engineering students from three universities, using an online survey and student interviews. The project used the framework of possible selves, in which students are motivated to achieve or avoid possible future selves (Bennett, forthcoming). A workshop to help prepare students for the workplace was developed, tested, and modelled.